The Role of E-learning in Medical Sciences Universities - M Ghasemi; M Ghazi Saidi; H Dargahi (Tehran University of Medical Sciences, 2008)
Background and Aim: Ever-increasing development of access to appropriate software and hardware for e-learning especially development of worldwide web has suggested new horizons for educational institutes. It is much important in medical sciences, because Medical Sciences deal with the health of human beings. Since beside issues related to education, research and information production, appropriate treatment of the patients is possible through having up to date and new information as well. For this reason Medical Sciences utilize information technology as soon as possible in order to prepare essential information for physicians quickly. This article discusses the role of e-learning in Medical Sciences universities.Materials and Methods: in this literature review article, gathering information has been done by using paper and paperless documents related to the topic.Results: For implementing of e-learning in Medical Sciences organization there should be some infra-structures, standards and skills which are to be noted prior to commencing e-learning. These infra-structures, standards and skills play a special role in successful implementation of e-learning.Conclusion: Regarding the advantages of e-learning naturally possesses, there is no doubt in necessity of developing Medical Sciences e-learning. But the ways of efficient access to this sort of education is much more important. So, it is recommended that by comparing the existing process in the world and using the experiences of prominent countries in this field, the most appropriate method be chosen and applied.